Accessing Arene-Fused Eight-Membered Carbo- and Heterocycles via Bidentate Lewis Acid Catalysis - Große, Michel; Justus Liebig University Giessen (My University, 2025)
Eight-membered carbo- and heterocycles constitute unique structural elements not only found in a plethora of biologically active natural products and medicinally relevant synthetic compounds, but also in various functional molecules and materials. Especially arene-annulated cyclooctanoids have attracted increasing attention as they combine the properties of rigid aromatic structures and flexible cyclooctene-derived ring systems. However, entropic and enthalpic difficulties generally encountered in the synthesis of medium-sized rings have largely hampered the development of general synthetic methods to access these structures. In this thesis, new strategies for the synthesis of arene-annulated eight-membered carbo- and N-heterocycles were developed by employing a boron-based bidentate Lewis acid (BDLA) catalyst previously established in our group for facilitating inverse electron-demand Diels−Alder (IEDDA) reactions of phthalazines. The utilization of different cyclooctyne derivatives as highly reactive dienophiles gave rise to a series of cyclooctenes and cycloocta-1,5-dienes fused to substituted polycyclic aromatic hydrocarbons. X-ray crystallographic analysis and variable temperature NMR studies of selected derivatives provided valuable insights into the conformational behaviour of these polycyclic structures. Additionally, the same catalytic principle was employed to develop a one-step synthesis of arene-annulated eight-membered nitrogen heterocycles from phthalazines and Boc-protected 2-azetine as a strained alkene dienophile. Key to this transformation was the formation of a highly reactive o-quinodimethane intermediate that thermally rearranged in a 10π electrocyclic ring opening to yield the desired azocine structures. These mechanistic considerations were supported by the isolation and characterization of the main by-product, and final proof for the eight-membered ring structure was obtained via X-ray crystallographic analysis of a degradation product.
Keywords: boron; nitrogen; catalysis; organic chemistry; ddc:540